Motivating relational organizing behavior for biodiversity conservation - Megan S. Jones; Rebecca M. Niemiec (Conservation Science and Practice, 2023)
Abstract As biodiversity loss and climate change accelerate, more people worldwide are engaging in conservation behaviors to “do their part.” Yet, individual behavior change alone is insufficient for the large‐scale, rapid change needed to address these crises. Relational organizing, which involves individuals reaching out to others in their social network, can enhance the speed and scale of conservation behavior change and address the complex, collective action nature of many conservation problems. However, many people practicing conservation behaviors in their own lives do not engage in relational organizing about conservation issues. Here, we suggest this may be the result of specific social‐psychological factors inhibiting people from reaching out to others. We summarize the evidence and offer a research and practice agenda to prioritize (1) understanding the social‐psychological barriers that prevent relational organizing, and (2) addressing these barriers through targeted outreach interventions to help scale and accelerate community action for conservation.